Rested, friendly, and engaged: The role of daily positive collegial interactions at work. (10th May 2017) - McGrath, Eugenia; Cooper‐Thomas, Helena D.; Garrosa, Eva; Sanz‐Vergel, Ana I.; Cheung, Gordon W.
Summary: This diary study examined within‐person effects of positive work and off‐work experiences on daily work engagement. Assessing the gain cycle assumption of conservation of resources theory, we investigated the relationship of nighttime recovery experiences and subsequent resources including elevated sleep quality and morning positive affect; the relationship of morning positive affect with positive collegial interactions and subsequent work engagement; and the relationship of work engagement with nighttime recovery experiences. Sixty‐nine employees completed 3 daily questionnaires over 5 consecutive working days. Multilevel analyses revealed that sleep quality positively predicted morning positive affect, which in turn predicted work engagement directly and also indirectly through having positive interactions with colleagues. Work engagement positively predicted nighttime recovery experiences, whereas nighttime recovery experiences were not related to sleep quality or morning positive affect the next day. Overall, on days after a good night's sleep, individuals feel more positive, bring this positivity to their workplace, reach out to their workplace colleagues, and are in turn more likely to be engaged in their work. Additionally, on days when individuals experience higher levels of positive collegial interactions at work and in turn higher work engagement, they are likely to enjoy better recovery experiences.